Strict Anatomical Colocalization of Vitiligo and Elastolytic Granulomas - de Paz, N. Merino (S. Karger AG, 2010)
Vitiligo is the most common depigmenting disorder, with a worldwide occurrence of 0.1-2% in the general population. Multiple conditions have been described colocalized in vitiligo patches, like psoriasis or lichen planus. However, actinic granuloma has not been described in association with vitiligo lesions so far.